2009
DOI: 10.17221/76/2009-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Detection of toxigenic Clostridium difficile in pig feces by PCR

Abstract: ABSTRACT:The ability to perceive the near ultraviolet part of the light spectrum (the wavelength 320-400 nm) has been detected in many bird species. This ability is an important bird sense. The ecological importance of UV perception has been studied mainly in the context of intra-and inter-sexual signalling, common species communication and also in foraging. Some birds of prey use UV reflectance in their feeding strategy: e.g., the kestrel (Falco tinnunculus), but also other birds of prey are able to recognize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Clostridium spp. were isolated from the gastrointestinal tract of pigs, and are abundant at relatively early stages of decomposition ( Varel et al , 1995 ; Alvarez-Perez et al , 2009 ; Garcia et al , 2009 ). Although most of the bacteria detected are anaerobic, the proportion of the aerobic bacterium Comamonas kerstersii was increased at week 6.…”
Section: Resultsmentioning
confidence: 99%
“…Clostridium spp. were isolated from the gastrointestinal tract of pigs, and are abundant at relatively early stages of decomposition ( Varel et al , 1995 ; Alvarez-Perez et al , 2009 ; Garcia et al , 2009 ). Although most of the bacteria detected are anaerobic, the proportion of the aerobic bacterium Comamonas kerstersii was increased at week 6.…”
Section: Resultsmentioning
confidence: 99%
“…Except for an in-house-developed semiautomatic PCR method to detect the C. difficile toxin genes A (tcdA) and B (tcdB), and a C. difficile specific triose phosphate isomerase (tpi) housekeeping gene, real-time PCR methods have not been evaluated to diagnose animal CDI (1). The aim of the present study was to compare the test performances of three different immunological assays and one molecular test to the CTA and toxigenic culture as the gold standards.…”
mentioning
confidence: 99%
“…Previous studies reported that C. difficile could be an etiological agent of enteritis in neonatal piglets [ 90 , 91 , 92 ]. While it is not considered to be a primary diarrheic pathogen in pigs based on epidemiological studies [ 93 , 94 , 95 , 96 ], other studies indicate that C. difficile is an emerging pathogen in neonatal diarrhoea [ 1 , 97 , 98 ]. These findings highlight the need for farmers to use recently developed commercial vaccines that provide immunization against C. difficile to sows to prevent neonatal diarrhoea via passive immunity.…”
Section: Discussionmentioning
confidence: 99%